2008
DOI: 10.1007/s11127-008-9358-y
|View full text |Cite
|
Sign up to set email alerts
|

Political competition and economic performance: evidence from the Italian regions

Abstract: Political competition, Growth, Redistribution, Regional government, D78, H71, H72, O17,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
49
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(54 citation statements)
references
References 16 publications
4
49
0
1
Order By: Relevance
“…Articles investigating the influence of candidates' personal valence indicate that if voters consider such aspects, politicians have a potential leeway in their decisions (see Groseclose, 2001;Adams et al, 2010;Padovano, 2013). Apart from pure electoral competition (see Downs, 1957aDowns, , 1957b, legislative choices and the behavior of politicians may be explained by other factors, such as gender (see Gagliarducci and Paserman, 2012;Stadelmann et al, 2014), having daughters (see Washington, 2008), links to civil service (see Braendle and Stutzer, 2010), education (see Ruske, 2015), and numerous other socioeconomic characteristics and preferences (see, e.g., Ågren et al, 2007;Padovano and Ricciutti, 2009;Freier and Thomasius, 2012;Okulicz-Kozaryn, 2014). Important contributions in political science and sociology turned their attention relatively early to the question of whether military service and know-how specific to the use of force affect the political willingness to support military action (see Huntington, 1957;Nordlinger, 1977).…”
Section: Related Literature and Theoretical Considerationsmentioning
confidence: 99%
“…Articles investigating the influence of candidates' personal valence indicate that if voters consider such aspects, politicians have a potential leeway in their decisions (see Groseclose, 2001;Adams et al, 2010;Padovano, 2013). Apart from pure electoral competition (see Downs, 1957aDowns, , 1957b, legislative choices and the behavior of politicians may be explained by other factors, such as gender (see Gagliarducci and Paserman, 2012;Stadelmann et al, 2014), having daughters (see Washington, 2008), links to civil service (see Braendle and Stutzer, 2010), education (see Ruske, 2015), and numerous other socioeconomic characteristics and preferences (see, e.g., Ågren et al, 2007;Padovano and Ricciutti, 2009;Freier and Thomasius, 2012;Okulicz-Kozaryn, 2014). Important contributions in political science and sociology turned their attention relatively early to the question of whether military service and know-how specific to the use of force affect the political willingness to support military action (see Huntington, 1957;Nordlinger, 1977).…”
Section: Related Literature and Theoretical Considerationsmentioning
confidence: 99%
“…Using a dataset on the outside earnings of the members of the German Federal Assembly, Becker et al (2009) find that politicians facing weak competition have substantially higher outside earnings. Padovano and Ricciuti (2009), instead, examine the effects of political competition on the economic performance of Italian regions. They use the electoral margin between the two largest parties as a measure of competition and show that regions where competition is stronger tend to grow faster.…”
mentioning
confidence: 99%
“…Padovano and Ricciuti (), as well as Besley and Case () and Svensson (), find similar results that greater political competition might lead to the adoption of pro‐growth policies. Dash and Mukherjee () have lately suggested that politically competitive Indian States perform well in terms of the Human Development Index, while Padovano and Ricciuti (), on a sample of the OED countries, find that greater political competition depresses growth. Comeau () and Plumper and Martin () also provide empirical evidence in favour of the inverted U‐shaped relation between economic growth and democracy.…”
Section: Introductionmentioning
confidence: 61%
“…In the empirical literature, a number of measures of political competition have been proposed. The mostly used is the ‘win margin’ (Holbrook and Van Dunk, ; Rogers and Rogers, ; Padovano and Ricciutti, ; Besley et al , ; Dash and Mukherjee, ). We, instead, propose two more suitable measure of political competition according to the following reasoning.…”
Section: Introductionmentioning
confidence: 99%